Radiology for PET/CT Reporting - Nanni, Cristina; Fanti, Stefano; Zanoni, Lucia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Reading PET/CT scans is sometimes challenging. Not infrequently, abnormal findings on CT images are functionally silent and therefore difficult for nuclear medicine practitioners to interpret. Furthermore, in general only a low-dose CT scan is produced as part of the combined PET/CT study, and the resulting CT images may prove suboptimal for image interpretation. This atlas is designed to enable nuclear medicine practitioners who routinely read PET/CT scans to recognize the most common CT abnormalities. Slice-by-slice descriptions are provided of anatomical structures as visualized on CT scans obtained in PET/CT studies. The CT findings that may be detected while reviewing PET/CT scans of various body regions and conditions are then illustrated and fully described. The concluding section of the book is devoted to the principal MRI findings in diseases which cannot be evaluated using PETs/CTs.
Normal CT slice by slice: Brain -- Head and neck -- Thorax -- Abdomen -- Pelvis -- Para-physiological CT findings: Brain -- Head and neck -- Thorax -- Abdomen -- Pelvis -- Pathologic CT findings: Brain -- Head and neck -- Thorax -- Abdomen -- Pelvis -- MR for nuclear medicine: Brain -- Bone -- Pelvis.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Medicine & Public Health; Nuclear Medicine; Imaging / Radiology